Pameran sebagai Ajang Mengembangkan Kreatifitas Mahasiswa dalam Mata Kuliah Pembelajaran Seni Rupa & Kerajinan - Zulmi Aryani; Maesaroh Lubis (Medan Resource Center, 2022)
This study aims to describe the exhibition activities carried out by students and their impact on creativity. This student exhibition is part of a course assignment. The approach used in this study is library research. data collection is carried out by reviewing and/or exploring journals, books, and documents (both printed and electronic) and other sources of data and/or information that are related to the focus of the study. In fact, this activity that produces student work reflects an increase in student creativity. It can be concluded based on their knowledge of the grade of their creation as a result of students' opportunities to assess and respond to their work.